A GENOME-WIDE ASSOCIATION STUDY IN PROGRESSIVE SUPRANUCLEAR PALSY. Issue 11 (14th October 2015) - Chen, Zhongbo; Shatunov, Aleksey; Bensimon, Gilbert; Payan, Christine; Ludolph, Albert; Leigh, Nigel; Group, NNIPPS Study; Al-Chalabi, Ammar
Abstract : Background: Progressive supranuclear palsy (PSP) is a debilitating Parkinsonian movement disorder characterised by tau protein burden. We aimed to identify common genetic variants influencing PSP susceptibility through a genome-wide association analysis (GWAS) of a multi-centre European study, Neuroprotection and Natural History in Parkinson's Plus Syndromes (NNIPPS), recruiting clinically well-characterised patients. We combined this with a meta-analysis of previously-identified gene variants. Methods: We genotyped 275, 684 single nucleotide polymorphisms using Illumina microarrays in 212 PSP cases from the UK, Germany and France, and compared these with 4, 707 matched controls. GWAS was performed using PLINK. Meta-analysis was performed with METAL. Genome-wide significance was defined as p<5×10^–8. Results: We observed multiple associations on chromosome 17 within or close to the MAPT gene, a well-established risk locus for PSP, confirming the sample and method validity. Of nine other previously reported associations, meta-analysis only confirmed that the MOBP variation (rs1768208) modified PSP risk (p=3.29×10^–13). Conclusion: In the GWAS and meta-analysis, we found the chromosome 17 inversion region to be associated with PSP susceptibility. Furthermore, we have shown that MOBP can modify the risk of PSP, possibly through influencing oligodendrocyte tau inclusions. These identified gene variants provide novel insights into the underlying genetics of sporadic PSP.